2018
DOI: 10.1002/bdr2.1350
|View full text |Cite
|
Sign up to set email alerts
|

Bone development in laboratory mammals used in developmental toxicity studies

Abstract: Evaluation of the skeleton in laboratory animals is a standard component of developmental toxicology testing. Standard methods of performing the evaluation have been established, and modification of the evaluation using imaging technologies is under development. The embryology of the rodent, rabbit, and primate skeleton has been characterized in detail and summarized herein. The rich literature on variations and malformations in skeletal development that can occur in the offspring of normal animals and animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 135 publications
(185 reference statements)
4
17
0
Order By: Relevance
“…88,89 The bilateral ossification centers or a dumbbellshaped structure in vertebrae or sternum of the fetuses of dams treated with Ara-C (Figure 6a and Figure 7a) clearly indicates the impaired ossification. 90 In agreement with previous reports, Ara-C prenatal treatment in our study also demonstrated fetal growth retardation as reveled by above said indicators. Further, the elevated OS is believed to implicate in pathological process of bone related disorders including bone loss through perturbing the orchestrated action of osteoclasts, osteoblasts and osteocytes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…88,89 The bilateral ossification centers or a dumbbellshaped structure in vertebrae or sternum of the fetuses of dams treated with Ara-C (Figure 6a and Figure 7a) clearly indicates the impaired ossification. 90 In agreement with previous reports, Ara-C prenatal treatment in our study also demonstrated fetal growth retardation as reveled by above said indicators. Further, the elevated OS is believed to implicate in pathological process of bone related disorders including bone loss through perturbing the orchestrated action of osteoclasts, osteoblasts and osteocytes.…”
Section: Discussionsupporting
confidence: 94%
“…The bilateral ossification centers or a dumbbell-shaped structure in vertebrae or sternum of the fetuses of dams treated with Ara-C (Figure 6a and Figure 7a) clearly indicates the impaired ossification. 90…”
Section: Discussionmentioning
confidence: 99%
“…Some skeletal variations ( Table 6 ) also occurred either in the AS03-adjuvanted CoVLP or placebo groups. The incidence of each observation was within historical control range of the testing facility, and these findings were considered to be of a spontaneous nature and were therefore not considered related to the administration of the vaccine candidate [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…These differences in origin and insertion of the abdominal muscles are largely due to the different skeletal structures in humans compared to other mammals. For instance, dogs, cats and rats exhibit a 13 th rib that is absent in humans which serves as an attachment site for the abdominal muscles [11,[46][47][48][49]. This is again seen in pigs with 15 to 17 ribs and horses who have 18 ribs [31,38].…”
Section: Musculaturementioning
confidence: 99%